Method for producing bonding composition

Copper particles are generated by wet reduction method and the liquid medium is replaced in a wet state to prepare a bonding composition with excellent adhesion, which solves the problem of insufficient adhesion during sintering in the prior art.

CN115297978BActive Publication Date: 2025-02-14MITSUI MINING & SMELTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180021804.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-03-12
Publication Date
2025-02-14
Estimated Expiration
2041-03-12

AI Technical Summary

Technical Problem

The prior art has insufficient adhesion between metal powder or conductive paste and other components during sintering, resulting in unsmooth coating film and poor adhesion.

Method used

Copper particles were generated in the first liquid medium by wet reduction method, and the wet state of the dispersion was maintained, and the first liquid medium was replaced with the second liquid medium, and a bonding composition containing the copper particles and the second liquid medium was prepared.

Benefits of technology

Excellent adhesion with other components during sintering is achieved, aggregation and deterioration of copper particles is reduced, and smoothness and adhesion of the coating film is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115297978B_ABST
    Figure CN115297978B_ABST
Patent Text Reader

Abstract

The present invention is a method for producing a bonding composition comprising copper particles and a second liquid medium. In the present production method, the copper particles are generated in a first liquid medium by a wet reduction method, thereby preparing a dispersion of the copper particles. Then, while maintaining the wet state of the dispersion, the first liquid medium of the dispersion is finally replaced with a second liquid medium. It is also preferred to replace the first liquid medium with other liquid media more than once and use the second liquid medium in the final replacement. It is also preferred to replace the liquid medium at a temperature below 100°C. As the second liquid medium, it is also preferred to use one or more of water, alcohol, ketone, ester, ether and hydrocarbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a bonding composition. Background Art

[0002] As electronic devices become smaller and more powerful, when electronic circuits are formed in electronic devices, various properties such as dimensional stability, conductivity, and adhesion to components are required to be improved. In order to achieve these requirements, for example, a conductive paste containing a metal powder with little aggregation between particles is desired.

[0003] Patent Document 1 discloses a method for producing a conductive paste, the method comprising: a step of precipitating metal powder by a wet reduction method; and a step of adding a water-soluble organic solvent to the metal powder with moisture attached thereto to replace the moisture with the water-soluble organic solvent.

[0004] Patent Document 2 discloses a method for producing a metal powder for a conductive paste, in which the metal powder is simultaneously pulverized and washed with water or an organic solvent.

[0005] Each of the above-mentioned patent documents also discloses that the dispersibility of metal powder can be improved.

[0006] In addition, Patent Document 3 discloses a method for producing a silver-containing powder by vacuum freeze-drying a dispersion of silver-containing particles and a surfactant.

[0007] Furthermore, Patent Document 4 discloses a silver powder obtained by treating silver particles obtained by a wet reduction method as a wet cake having a predetermined moisture content, adding a dispersant to the wet cake, and pulverizing the wet cake.

[0008] Like Patent Documents 1 and 2, these Patent Documents also disclose that the dispersibility of metal powder can be improved.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2003-151381

[0012] Patent Document 2: Japanese Patent Application Publication No. 2003-253301

[0013] Patent document 3: US2009 / 146117A1

[0014] Patent Document 4: Japanese Patent Application Publication No. 2007-224422 Summary of the invention

[0015] The techniques described in Patent Documents 1 to 4 all examine the dispersibility of metal particles, but do not examine the adhesion with other members when the obtained metal powder or the conductive paste containing the metal powder is used and sintered.

[0016] An object of the present invention is to provide a method for producing a bonding composition having excellent adhesion to other members during sintering.

[0017] The present invention provides a method for producing a bonding composition, wherein copper particles are generated in a first liquid medium by a wet reduction method to prepare a dispersion of the copper particles, and then,

[0018] The first liquid medium of the dispersion is finally replaced with the second liquid medium while maintaining the wet state of the dispersion, thereby obtaining a bonding composition including the copper particles and the second liquid medium. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 (a) and (b) are ultrasonic images of sintered bodies obtained by sintering the bonding compositions of Examples and Comparative Examples together with objects to be bonded. DETAILED DESCRIPTION

[0020] Hereinafter, the present invention will be described based on its preferred embodiment. The method of the present invention relates to the manufacture of a bonding composition comprising copper particles and a second liquid medium. The bonding composition is suitable for use as a conductive paste or conductive ink for bonding two bonding objects to each other. In this case, the bonding composition is preferably a dispersion comprising copper particles as a conductive filler and a second liquid medium.

[0021] The manufacturing method of the present invention is roughly divided into two steps: a step of generating copper particles in a first liquid medium by a wet reduction method to prepare a dispersion of copper particles; and a step of finally replacing the first liquid medium of the dispersion with a second liquid medium while maintaining the wet state of the dispersion.

[0022] The "wet state" here means that the copper particles are not dried by, for example, heat treatment, and the surface of the copper particles is wet, and the gas phase and the copper particles are not in direct contact. Specifically, it means that the solid content concentration of the liquid medium dispersion of the copper particles is maintained at 95% by mass or less.

[0023] In addition, "finally replacing the first liquid medium with the second liquid medium" refers to two methods, including: directly replacing the first liquid medium with the second liquid medium, thereby obtaining a dispersion containing the second liquid medium as the final target; and replacing the first liquid medium with one or more other liquid media (excluding the first liquid medium and the second liquid medium) other than the second liquid medium, and in the final liquid medium replacement step, replacing the other liquid medium (excluding the first liquid medium and the second liquid medium) with the second liquid medium, thereby obtaining a dispersion containing the second liquid medium as the final target.

[0024] First, copper particles are generated in a liquid medium by a wet reduction method. In the wet reduction method, for example, a copper compound as a copper source and a reducing compound are mixed in a first liquid medium to prepare a reaction solution, and the copper compound in the reaction solution is reduced to obtain target copper particles. By using a wet reduction method to produce copper particles, the particle size of the particles can be easily controlled, and spherical particles can be easily obtained. For example, copper particles can also be produced by the method described in Japanese Patent Publication No. 2015-168878.

[0025] When preparing a reaction solution containing a copper compound and a reducing compound, there is no particular restriction on the order and method of adding the copper compound and the reducing compound. For example, a solid copper compound and a solid reducing compound can be added simultaneously to prepare the reaction solution. In addition, at least one of the copper compound and the reducing compound can be dispersed or dissolved in a liquid medium in advance, and then one is added to the other to prepare the reaction solution. When one of the copper compound and the reducing compound is added to the other, it can be added all at once, or it can be added continuously or intermittently by methods such as dropwise addition.

[0026] As the copper compound, a compound soluble in a liquid medium is preferably used. Examples of such copper compounds include water-soluble copper (II) salts such as copper chloride, copper acetate, and copper sulfate. These copper compounds may be anhydrous or hydrated. These copper compounds may be used alone or in combination.

[0027] The copper compound is mixed so that the content of the copper compound in terms of the copper element in the reaction solution is preferably 0.001 mol / L to 1 mol / L, more preferably 0.1 mol / L to 0.5 mol / L. By setting the content of the copper compound to such a level, copper particles with a small particle size can be obtained with high productivity.

[0028] The reducing compound reduces the copper ions of the copper source. Examples of the reducing compound include hydrazine compounds such as hydrazine, hydrazine hydrochloride, hydrazine sulfate, and hydrazine hydrate, sodium borohydride, sodium sulfite, sodium bisulfite, sodium thiosulfate, sodium nitrite, sodium hyponitrite, phosphorous acid, sodium phosphite, hypophosphorous acid, and sodium hypophosphite. These reducing compounds may be anhydrous or hydrated. These reducing compounds may be used alone or in combination of two or more.

[0029] In particular, hydrazine is particularly preferably used because it generates less impurities after reduction and less impurities are mixed into the obtained copper particles. From the perspective of strong reducing power and suppression of impurities mixing into particles, it is more preferable to use only anhydrous hydrazine or hydrate of hydrazine as the reducing compound.

[0030] The content of the reducing compound in the reaction solution is preferably 0.5 mol or more and 50 mol or less, more preferably 1 mol or more and 10 mol or less, and further preferably 2 mol or more and 5 mol or less relative to 1 mol of the copper element. By setting the content of the reducing compound to such a ratio, copper particles with a small particle size can be easily obtained. The reduction of the copper compound using the reducing compound can be performed only once or multiple times as required. The content of the above-mentioned reducing compound is set to a value converted with anhydrous substances.

[0031] Regarding the reaction conditions of the reaction solution, the reaction may be carried out without heating from the start of mixing to the end of the reaction, or the reaction may be carried out under heating.

[0032] Furthermore, from the viewpoint of causing the reduction reaction to proceed uniformly and obtaining copper particles with less uneven particle size, it is also preferred to continue stirring the reaction solution throughout the entire time from the start of mixing to the end of the reaction.

[0033] From the perspective of both achieving a reduction reaction sufficient to form copper particles and reducing manufacturing costs, it is preferred to carry out the reaction in a manner that maintains a temperature of 0°C or higher and 80°C or lower from the start of mixing to the end of the reaction. The time from the start of mixing to the end of the reaction can be appropriately changed according to the particle size of the target copper particles, and can be preferably set to 0.5 hours or more and 4 hours or less, and more preferably 1 hour or more and 3 hours or less. When the reduction treatment of the copper compound using a reducing compound is performed multiple times, the above time is set as the total time from the start of mixing to the end of the reaction.

[0034] Copper particles are generated through the above steps. Since the copper particles are obtained by the wet reduction method, the copper particles are in a state of a dispersion of the copper particles dispersed in the first liquid medium, which is the liquid medium of the reaction solution.

[0035] The particle size of the generated copper particles was determined by analyzing the image observed by a scanning electron microscope and the cumulative volume at 50% by volume. SEM50 It is preferably 100 nm or more and 300 nm or less, and more preferably 100 nm or more and 250 nm or less. SEM50 The particle size of the primary particles of an object that is considered to be the smallest unit of particles, as judged from the geometric shape of the outer shape, therefore, by setting the copper particles to this particle size range, the bonding composition exhibits good filling and sintering properties, can exhibit high adhesion with other components such as the bonding object, and is conducive to forming a thinner coating film. The particle size of the copper particles can be appropriately adjusted by adjusting the molar ratio of the copper compound to the reducing compound, and the time of the reduction reaction, for example.

[0036] For example, D can be determined by the following method SEM50 First, the image data of copper particles observed from above using a scanning electron microscope was read using the software Mac-View manufactured by MOUNTECH. Then, 50 or more copper particles in the data were randomly selected to measure the particle size (projected circle area equivalent diameter). Next, the volume of the particle assuming that it is a true sphere was calculated from the obtained projected circle area equivalent diameter, and the volume cumulative particle size at 50% of the cumulative volume was taken as D. SEM50 .

[0037] Next, while maintaining the wet state of the copper particle dispersion, the first liquid medium of the dispersion is replaced with the second liquid medium. In this process, one of its characteristics is that when obtaining the target bonding composition, while maintaining the wet state of the dispersion, the first liquid medium in the dispersion is replaced with the second liquid medium that is the liquid medium finally contained in the bonding composition.

[0038] In the process of preparing a conductive paste, conductive ink or other bonding composition containing copper particles as conductive fillers, typically, a dry copper powder obtained by drying the obtained copper particles is used. In this method, by appropriately increasing or decreasing the content of copper particles, a paste or ink with a desired filler concentration can be easily prepared. However, in the case of using dry copper powder to prepare a bonding composition, the copper particles in the dry copper powder aggregate or become easily aggregated, thereby causing the redispersion process to become complicated, and sometimes redispersion itself becomes impossible. As a result, the coating obtained by applying the bonding composition is difficult to become smooth, and the adhesion to other components is poor. In addition, when drying, the surface of the copper particles is sometimes deteriorated due to oxidation, etc., so that the desired characteristics such as adhesion and conductivity cannot be exerted.

[0039] In particular, when copper particles having a particle size suitable for ink or paste are used in a dry state, the complexity of redispersion and the deterioration of particles due to oxidation and the like become significant.

[0040] In order to solve this problem, the inventors have conducted research, and as a result, the copper particles obtained are not dried, but maintained in a wet state and directly supplied to subsequent processes, thereby reducing the contact between the copper particles and oxygen in the atmosphere. In addition, the dispersibility of the copper particles when preparing the bonding composition becomes higher, thereby suppressing the excessive stress generated during film formation and sintering. It was found that the bonding composition of the present invention exhibits excellent adhesion with other components during sintering, and can suppress the peeling from other components caused by excessive volume shrinkage during sintering.

[0041] The first liquid medium may be directly replaced with the second liquid medium (hereinafter referred to as "direct replacement"), or the first liquid medium may be replaced with another liquid medium (but not including the second liquid medium) one or more times and then finally replaced with the second liquid medium (hereinafter referred to as "indirect replacement"). The dispersions maintained in a wet state may be in the form of slurry or wet cake, for example, independently.

[0042] The replacement method of the liquid medium, whether direct replacement or indirect replacement, is not particularly limited as long as the wet state of the dispersion can be maintained, and for example, reslurry washing, decantation, rotary filtration, filtration, etc. can be used. In addition, the replacement of the liquid medium can be performed only once or multiple times as needed.

[0043] Regardless of whether the replacement is direct or indirect, the replacement of the liquid medium is preferably performed at a temperature of the liquid medium of less than 100° C., more preferably less than 80° C., and further preferably less than 60° C. By setting such a temperature, the evaporation of the liquid medium during the replacement can be suppressed, the wet state and high dispersibility of the copper particles can be maintained, and a bonding composition with excellent adhesion to other components can be obtained.

[0044] In the process of finally replacing the first liquid medium with the second liquid medium, from the perspective of effectively removing the components from the first liquid medium that may cause impurities and improving the operability of replacing with the second liquid medium contained in the target bonding composition, it is preferred to replace the first liquid medium contained in the copper particle dispersion obtained by the wet reduction method with other liquid media (but not including the first liquid medium and the second liquid medium) more than once, and use the second liquid medium in the final replacement. That is, as the present manufacturing method, it is preferred to adopt indirect replacement.

[0045] In addition, when the first liquid medium is replaced with other liquid media (but not including the second liquid medium) multiple times, it is preferred to maintain the wet state of the dispersion and perform the replacement in each process of replacement from the first liquid medium to the initial other liquid medium, replacement between other liquid media when using two or more other liquid media, and final replacement from other liquid medium to the second liquid medium.

[0046] When the first liquid medium is replaced with another liquid medium one or more times, the solid content concentrations in each replacement step are independent and may be the same or different.

[0047] By maintaining the copper particles in a wet state and replacing the liquid medium, components from the first liquid medium that may become the cause of impurities can be effectively removed, and copper particles with high redispersibility and little deterioration can be obtained. Therefore, when a bonding composition containing the copper particles is sintered, a bonding composition with excellent adhesion to other components can be obtained.

[0048] As one embodiment of the method of replacing the first liquid medium with another liquid medium one or more times, for example, there is a method of washing the first liquid medium dispersion of copper particles obtained by a wet reduction method with another liquid medium such as water.

[0049] When the cleaning treatment is performed, the method may be, for example, reslurry cleaning, decantation, rotary filtration, filtration, etc. When the cleaning treatment is performed, it is preferred that the copper particles after cleaning are provided to the subsequent step in the state of a dispersion maintaining a wet state.

[0050] When the copper particles are cleaned by decantation, for example, another liquid medium is added and cleaned until the conductivity of the dispersion is preferably less than 5 mS. The cleaning conditions at this time are, for example, when water is used as the other liquid medium, the cleaning temperature is preferably set to less than 100°C, more preferably to 15°C or more and 30°C or less. By carrying out under such conditions, the impurities contained in the copper particles can be reduced, and the particles can be provided to the subsequent process in a state where they are uniformly dispersed. Then, the liquid medium dispersion of the cleaned copper particles is finally replaced with the second liquid medium in a state where the wet state is maintained.

[0051] As other embodiments of the method of replacing the first liquid medium with another liquid medium more than once, for example, the method described in the embodiment described later can be cited, but as long as the effect of the present invention can be exerted, it can be applied, and there is no particular limitation on the number of replacements and the type of liquid medium used. Then, the liquid medium dispersion of copper particles is finally replaced with the second liquid medium in a state where it is maintained in a wet state.

[0052] Through the above-mentioned steps, a bonding composition comprising copper particles and the second liquid medium can be obtained. According to this manufacturing method, the dispersion treatment of the copper particles when preparing the bonding composition becomes simple, and the aggregation of the copper particles is reduced, so a coating film with high smoothness can be efficiently formed. In addition, the deterioration of the surface of the copper particles can be reduced. As a result, when the coating film formed by the bonding composition is sintered, the fusibility of the copper particles can be improved, the fusibility of the copper particles can be improved, and the contact area between the molten particles and other components can be increased. As a result, a sintered body that is difficult to generate cracks and peeling and has excellent adhesion with other components can be obtained.

[0053] As the first liquid medium used in the present manufacturing method, from the perspective of effectively reducing copper by a wet reduction method, one or more of water, alcohol, ketone, ester and ether is preferred, and from the perspective of improving compatibility with copper salts and improving the efficiency of copper particle generation in the manufacture of copper particles by a wet reduction method, one or more of water and alcohol is more preferred.

[0054] In addition, as the second liquid medium used in the present manufacturing method, from the perspective of being able to use the bonding composition directly as a conductive paste or conductive ink to improve productivity, one or more of water, alcohol, ketone, ester, ether and hydrocarbon are preferred, and alcohol and hydrocarbon are more preferred.

[0055] It should be noted that the first liquid medium and the second liquid medium may be the same as or different from each other.

[0056] From the perspective of balancing the reduction of the residual amount of the first liquid medium and the ease of replacement with the second liquid medium, when using other liquid media (but not including the first liquid medium and the second liquid medium), it is preferred to use one or more of water, alcohol, ketone, ester, ether and hydrocarbon as the other liquid medium, and it is more preferred to use one or more of water and alcohol.

[0057] As the alcohol, for example, polyols such as monohydric alcohols such as methanol, ethanol, n-propanol, 2-propanol and n-butanol, dihydric alcohols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, butanediol, pentanediol and hexanediol, trihydric alcohols such as glycerol, and polyhydric alcohols such as polyethylene glycol and polypropylene glycol can be used.

[0058] Examples of the ester include fatty acid esters of the above-mentioned polyhydric alcohols. Examples of the fatty acid include monovalent fatty acids having preferably 1 to 8 carbon atoms, more preferably 1 to 5 carbon atoms. The polyhydric alcohol ester preferably has at least one hydroxyl group.

[0059] The ketone is preferably a ketone in which the number of carbon atoms of the alkyl group bonded to the carbonyl group is 1 to 6, particularly 1 to 4. Specific examples of the ketone include methyl ethyl ketone and acetone.

[0060] Examples of the ether include chain ethers such as dimethyl ether, ethyl methyl ether, and diethyl ether, and cyclic ethers such as oxetane, tetrahydrofuran, and tetrahydropyran.

[0061] Examples of the hydrocarbon include aliphatic hydrocarbons such as hexane, heptane, octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, and hexadecane.

[0062] In the case of direct replacement, the first liquid medium and the second liquid medium used are preferably compatible with each other under the conditions of 1 atmosphere and 25° C. Compatibility refers to a phenomenon in which two or more liquid components in a fluid containing two or more liquid components are mixed to form a single phase.

[0063] By using a compatible liquid medium, the first liquid medium can be replaced with the second liquid medium while maintaining the dispersibility of the particles in the copper particle dispersion. On this basis, the second liquid medium can be replaced while reducing the deterioration of the copper particles. Therefore, when the obtained bonding composition is sintered, the fusibility of the copper particles can be improved, and the contact area between the molten particles and the surface of other components can be increased. As a result, a sintered body with high adhesion to other components and less impurities can be obtained.

[0064] In addition, in the case of indirect replacement, when the first liquid medium is replaced with other liquid media more than once, it is preferred that the first liquid medium and the initial other liquid medium, the other liquid media continuously in the process when the other liquid medium is replaced more than twice, and the combination of the last other liquid medium and the second liquid medium are compatible with each other, and more preferably they are compatible with each other under the conditions of 1 atmosphere and 25°C.

[0065] In the case of indirect replacement, the first liquid medium and the second liquid medium may be compatible with each other under the conditions of 1 atmosphere and 25° C., or may be incompatible with each other under the conditions.

[0066] By using compatible liquid media for replacement of each liquid medium, components from the first liquid medium and other liquid impurities that may cause impurities can be effectively removed. As a result, a sintered body with high adhesion to other components and less impurities can be obtained.

[0067] In addition, as one of the indirect replacement methods, the liquid medium may be replaced with another liquid medium (but not including the first liquid medium and the second liquid medium) having a lower viscosity than the first liquid medium, thereby reducing the impurities in the dispersion, and finally replaced with a second liquid medium having a higher viscosity than the other liquid medium (but not including the first liquid medium and the second liquid medium). For example, the viscosity of the liquid medium may be measured by a vibration viscometer or a rotational viscometer.

[0068] In the above-mentioned steps of generating copper particles by wet reduction method, replacing the first liquid medium with the second liquid medium, replacing the first liquid medium with other liquid medium as needed, and replacing the second liquid medium with other liquid medium, it is preferred to carry out in the absence of organic polymers, and more preferably, in all the steps of the manufacturing method of the present invention, it is carried out in the absence of organic polymers.

[0069] In the present production method, in order to eliminate the presence of organic polymers in the reaction system, for example, in each step of the reducing wet method and the liquid medium replacement, an organic polymer and a raw material containing the organic polymer may be used.

[0070] By performing each step in the absence of an organic polymer, the aggregation degree of the copper particles is maintained at a low state, and when the bonding composition is sintered, the copper particles can be fully sintered. On this basis, the content of residual organic matter that is one of the impurities and can become a sintering inhibitor can be reduced, so the density is high and the adhesion with other components is more excellent.

[0071] Examples of the organic polymer include natural polymers and synthetic polymers used as dispersants and surface treatment agents in the technical field. Specifically, examples include natural polymers such as proteins such as gelatin, gum arabic, casein, sodium caseinate, ammonium caseinate, starch, dextrin, agar, and sodium alginate. Examples of synthetic polymers include cellulose compounds such as hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, and ethyl cellulose, polyvinyl compounds such as polyvinyl alcohol, and polyacrylic acid compounds such as sodium polyacrylate and ammonium polyacrylate.

[0072] The bonding composition obtained through the above process is a dispersion containing copper particles and a second liquid medium. The bonding composition may contain only the second liquid medium as the liquid medium constituting the composition, or in addition to the second liquid medium, may inevitably contain the liquid medium used in the liquid medium replacement so far. In either case, it is preferred that the second liquid medium contained is the largest in terms of mass ratio among all the liquid media constituting the bonding composition.

[0073] The bonding composition can be used directly, or at least one of metal particles other than copper particles, a liquid medium, and a binder resin contained in the bonding composition can be further added as needed to use it in the form of a conductive paste, a conductive ink, etc. That is, the present invention also includes a method for producing a conductive paste: comprising at least the bonding composition obtained through the above steps, and further mixing the bonding composition with at least one of metal particles other than copper particles, a liquid medium, and a binder resin contained in the bonding composition as needed.

[0074] Examples of the metal particles that may be further added to the bonding composition include particles containing metals such as copper, silver, and gold.

[0075] As the liquid medium that may be further added to the bonding composition, for example, the same liquid medium as exemplified in the description of the first liquid medium and the second liquid medium and having good compatibility with the binder resin may be used.

[0076] Examples of the binder resin that may be further added to the bonding composition include one or more of acrylic resins, epoxy resins, polyester resins, polycarbonate resins, and cellulose resins.

[0077] The bonding composition can be configured by coating or the like between any two materials to be bonded by a prescribed means, and two materials to be bonded are bonded to each other to form a bonding structure. That is, the present invention also includes a method for configuring a bonding composition between two materials to be bonded to bond the materials to be bonded, and a method for manufacturing a bonding structure. As the materials to be bonded, substrates, semiconductor elements, etc. can be used independently. As a specific embodiment, for example, it can be used as a bonding agent when the surface of an electronic device is mounted on a printed wiring board, a material for filling a through-hole in a printed wiring board. In addition, a wiring circuit of a printed wiring board or an electrode for forming a chip component can be formed.

[0078] The present invention has been described above based on the preferred embodiments of the present invention, but the present invention is not limited to the above embodiments. For example, for copper particles obtained by wet reduction method, as long as the effect of the present invention can be exerted, it is not excluded that the obtained copper particles inevitably contain trace amounts of other elements and the surface of the copper particles is inevitably oxidized in trace amounts.

[0079] Example

[0080] Hereinafter, the present invention will be described in more detail by way of examples, but the scope of the present invention is not limited to these examples.

[0081] [Example 1]

[0082] In the present example, the bonding composition was produced in the absence of an organic polymer in any of the steps.

[0083] (1) Generating copper particles using wet reduction method

[0084] In a 36-liter stainless steel tank, a mixed liquid medium of 5.0 liters of warm pure water and 5.0 liters of methanol as the first liquid medium and 2.5 kg of copper acetate as a copper source were added, and stirred at a liquid temperature of 40°C for 30 minutes to dissolve the copper acetate. Then, 150 g of hydrazine was added to the liquid medium at one time, and then stirring was continued for 30 minutes at a liquid temperature of 40°C to generate cuprous oxide particles in the liquid medium. After 30 minutes, 1400 g of hydrazine was further added to the liquid medium at one time, and then stirring was continued for 60 minutes at a liquid temperature of 40°C to reduce the fine particles of cuprous oxide to fine particles of metallic copper. In this way, a dispersion in which copper particles are dispersed in the first liquid medium is obtained. The dispersion is maintained in a wet state. The particle size D of the obtained copper particles is SEM50 It is 155nm.

[0085] (2) Replacement of liquid medium

[0086] In this embodiment, the first liquid medium is replaced by another liquid medium a plurality of times, and then, as the final replacement, the second liquid medium is replaced. All steps are performed while the dispersion is maintained in a wet state.

[0087] Specifically, pure water compatible with the first liquid medium is used as the first other liquid medium. The first liquid medium dispersion of copper particles is washed with pure water by decantation until the conductivity becomes 3.5 mS, thereby obtaining a first dispersion in which copper particles are dispersed in water. The first dispersion is maintained in a wet state.

[0088] Next, as the second other liquid medium, a modified alcohol (a mixed liquid medium of 89 mass % ethanol and 11 mass % 2-propanol) compatible with the first other liquid medium is used. A rotary filter is used to perform a washing process with the modified alcohol until the water concentration in the first dispersion becomes 1 mass % or less, thereby obtaining a second dispersion in which copper particles are dispersed in the modified alcohol. The second dispersion is maintained in a wet state.

[0089] Next, hexylene glycol, which is compatible with the second other liquid medium, is used as the second liquid medium used in the final replacement. A washing treatment is performed with hexylene glycol using a rotary filter until the concentration of the modified alcohol in the second dispersion becomes 3% by mass or less, and then the hexylene glycol is separated from the solid and liquid by pressure filtration to obtain a bonding composition in which copper particles are dispersed in the second liquid medium. The bonding composition maintains a wet state with a solid content concentration of 92%.

[0090] (3) Preparation of bonding paste

[0091] 7.6 parts by mass of a joining composition, 3 parts by mass of metal particles other than the copper particles contained in the joining composition (copper particles, 1200YF, manufactured by Mitsui Mining & Smelting Co., Ltd.), 0.5 parts by mass of a BIS-TRIS / hexanediol solution having a solid content concentration of 50% by mass, and 0.1 parts by mass of polyethylene glycol 300 were mixed, and hexanediol was used as the balance to prepare a joining paste containing copper particles in a manner such that the concentration of the copper particles was 76% by mass.

[0092] [Comparative Example 1]

[0093] As in Example 1, (1) after the copper particles were generated by the wet reduction method, the first liquid medium dispersion of the copper particles was washed with pure water by decantation until the conductivity was 3 mS, thereby obtaining a dispersion of the copper particles dispersed in water. The dispersion was maintained in a wet state.

[0094] Next, the dispersion was heated to 50° C., and a dimethylglyoxime / methanol solution was added while stirring so that the dimethylglyoxime content was 0.5% by mass relative to the copper particle content. The mixture was stirred at a liquid temperature of 50° C. for 1 hour to obtain a water / methanol dispersion of surface-treated copper particles.

[0095] Afterwards, the copper particles that have completed the surface treatment are vacuum dried to obtain dry copper particles, in which no liquid medium exists.

[0096] Finally, a joining paste having the same composition and concentration as in Example 1 was prepared using dried copper particles instead of the joining composition.

[0097] [Adhesion Evaluation]

[0098] The bonding pastes of Examples and Comparative Examples were screen-printed on the center of the surface of a copper plate (20 mm long x 20 mm wide x 2 mm thick) in a size of 10 mm long x 10 mm wide x 110 μm thick, and the bonding pastes were dried at 110° C. for 20 minutes to obtain a dry film.

[0099] Next, an alumina plate (5 mm in length × 5 mm in width × 0.5 mm in thickness) with Ag plated on the surface was placed on the dried film and sintered at 280°C for 20 minutes at 6 MPa and a heating rate of 120°C / min in a nitrogen atmosphere to bond the copper plate and the alumina plate.

[0100] After joining, an ultrasonic flaw detector (manufactured by Hitachi Power Solutions, model: FineSATIII) and a 75 MHz probe were used to observe the copper plate from the surface side where the alumina plate was arranged by reflection method to observe whether there were voids in the sintered body of the dry film and the state of the outer periphery (unpressed area) of the alumina plate in the sintered body of the dry film. It was observed that the denser the sintered structure, the darker the color. The results are shown in Figure 1 .

[0101] Figure 1 In the figure, the region where the alumina plate is arranged is indicated by symbol A, the region where the sintered body of the dry film exists is indicated by symbol B, and the region where the copper plate is exposed is indicated by symbol C.

[0102] like Figure 1 As shown in (a), in the sintered body of the paste obtained using the bonding composition of Example 1, it was observed that the color of the region A where the alumina plate was arranged was darker, so it was judged that a dense structure with few voids was formed, and the bonding state of the alumina plate and the copper plate was good. In addition, in the region B where the sintered body located at the periphery of the alumina plate existed, the color observed was uniform, and no peeling of the sintered body and the copper plate was observed. Therefore, it was judged that the paste using the bonding composition of Example 1 had excellent adhesion to other components.

[0103] On the other hand, Figure 1 As shown in (b), in the sintered body of the paste obtained using the bonding composition of Comparative Example 1, the color of the region A where the alumina plate is arranged is observed to be darker, so it is judged that the bonding state of the alumina plate and the copper plate is good, but the color observed in the sintered body located in the outer periphery of the alumina plate. The region B is uneven, and it is observed that the sintered body and the copper plate are peeled off. Therefore, it is judged that the paste using the bonding composition of Comparative Example 1 has poor adhesion to other components.

[0104] Industrial Applicability

[0105] According to the production method of the present invention, a bonding composition having excellent adhesion to other members during sintering can be obtained.

Claims

1. A method for producing a bonding composition, wherein: Copper particles are generated in a first liquid medium by a wet reduction method to prepare a dispersion of the copper particles, and then, while maintaining the wet state of the dispersion, the first liquid medium of the dispersion is finally replaced with a second liquid medium, thereby obtaining a bonding composition including the copper particles and the second liquid medium; wherein the first liquid medium is replaced with another liquid medium more than once, and the second liquid medium is used in the final replacement, Using water as the first liquid medium, Using monohydric alcohol as other liquid medium, Using polyol as the second liquid medium, The steps of replacing the first liquid medium with another liquid medium and replacing the second liquid medium with another liquid medium are performed in the absence of an organic polymer. The copper particles are generated in the absence of an organic polymer.

2. The manufacturing method according to claim 1, wherein: The replacement of the liquid medium is performed at a temperature below 100°C.

3. The manufacturing method according to claim 1 or 2, wherein: The replacement of the first liquid medium with another liquid medium is performed until the conductivity of the dispersion becomes 5 mS or less.

4. The manufacturing method according to claim 1 or 2, wherein: The cumulative volume particle size D at 50% of the cumulative volume of the copper particles measured by scanning electron microscopy is SEM50 It is greater than or equal to 100 nm and less than or equal to 300 nm.

5. The manufacturing method according to claim 1 or 2, wherein: The monohydric alcohol is at least one of methanol, ethanol, n-propanol, 2-propanol and n-butanol.

6. The manufacturing method according to claim 1 or 2, wherein: The polyol is at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, butylene glycol, pentanediol and hexanediol.

7. The manufacturing method according to claim 1, wherein: While maintaining the dispersion in a wet state, the first liquid medium is replaced with another liquid medium.

8. A method for producing a conductive paste, wherein: The conductive paste includes a bonding composition obtained by the production method according to any one of claims 1 to 7.

9. A method for joining materials to be joined, wherein: The joining composition obtained by the production method according to any one of claims 1 to 7 is disposed between two materials to be joined.

Citation Information

Patent Citations

  • Manufacturing method of conductive paste and conductive paste

    JP2003151381A

  • Method for manufacturing metal powder for conductive paste, metal powder for conductive paste, conductive paste, and multilayer ceramic electronic part

    JP2003253301A

  • Silver powder and paste using the same

    JP2007224422A

  • Copper powder

    JP2015168878A

  • Nanometric copper formulations

    EP3113897B1